UPAYA DIPLOMASI PUBLIK TURKI MELALUI INTERNATIONAL ISTANBUL FILM FESTIVAL - Arina Varadilla; Haydar Faiq Eryanto; Ario Bimo Utomo (Journal Publicuho, 2025)
This study explores how Turkey utilises the Istanbul International Film Festival (IIFF) as a public diplomacy tool to shape its international image. Using Nicholas J. Cull’s public diplomacy theory, particularly the aspect of cultural diplomacy, this research analyses how IIFF film festival serves as a cultural communication platforms that introduce Turkey’s values, identity, and narratives to global audiences. The study employs literature review, documentation of IIFF events, and content analysis of featured films and programs. The findings reveal that IIFF is not only a site of cultural exchange but also a strategic tool for the Turkish government to subtly convey political messages, extend cultural influence, and strengthen the country's position in international discourse. This strategy aligns with Turkey’s broader efforts to enhance its global soft power. The study concludes that cultural diplomacy through film festivals such as IIFF is an effective means of reinforcing national branding and fostering positive perceptions of Turkey on the world stage.